2020
DOI: 10.1093/ilar/ilab001
|View full text |Cite
|
Sign up to set email alerts
|

Current Topics in Marmoset Anesthesia and Analgesia

Abstract: Anesthetic and analgesics are essential components of both clinical and research procedures completed in marmosets. A review of current anesthetic and analgesic regimens for marmosets has been complied to provide a concise reference for veterinarians and investigator teams. Published dose regimens for injectable and inhalant anesthetic drugs and analgesic drugs are included. Appropriate physiological monitoring is key to the success of the procedure and perianesthetic options are provided. Although recent publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…In this study, no abnormal behaviors or clinical signs, or injection site reactions were observed. By comparison, PK studies in the common marmoset 10,11 using a polymer‐based compounded long‐acting SR‐BUP demonstrated mild localized erythema and swelling of tissues around the injection site, which was reversible over time. This was not observed with Ethiqa XR in marmosets 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no abnormal behaviors or clinical signs, or injection site reactions were observed. By comparison, PK studies in the common marmoset 10,11 using a polymer‐based compounded long‐acting SR‐BUP demonstrated mild localized erythema and swelling of tissues around the injection site, which was reversible over time. This was not observed with Ethiqa XR in marmosets 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetic and analgesic protocols should be optimized for specific animal species and experimental purposes. Diverse anesthetic and analgesic regimes for marmosets have been reviewed recently [45,46]; in this section, we describe our procedures and some cautionary notes based on our experience at CIEA. Table 2 lists the anesthetic protocols, including premedication, emergency drugs, and postoperative analgesic doses for marmosets currently in use at CIEA.…”
Section: Anesthesia and Analgesia Protocols In Marmosetsmentioning
confidence: 99%
“…BSM-3592, Nihon Kohden) are used. Other sensors of SpO2 designed for pediatric use or rodents are available for marmosets [46]. During a major surgery or long anesthesia, in addition to respiration, SpO2, and pulse, rectal temperature and electrocardiogram are monitored.…”
Section: Anesthesia and Analgesia Protocols In Marmosetsmentioning
confidence: 99%
“…The safe use of Telazol ® has already been documented in nonhuman primates including capuchin monkeys [ 11 , 12 ], owl monkeys [ 13 ], rhesus macaques [ 14 , 15 , 16 ], cynomolgus macaques [ 17 ], baboons [ 14 ], chimpanzees [ 18 , 19 , 20 ], and southern brown howler monkeys [ 21 ]. There are a few reports of Telazol ® administration to marmosets, showing a wide dose range [ 9 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. However, evidence-based sedation and anesthetic dose determination for marmosets have never been performed.…”
Section: Introductionmentioning
confidence: 99%